The expanded genome of Hexamita inflata, a free-living diplomonad - Zeynep Akdeniz; Michal Havelka; Michal Stoklasa; Alejandro Jiménez-González; Vojtěch Žárský; Feifei Xu; Courtney W. Stairs; Jon Jerlström-Hultqvist; Martin Kolísko; Jan Provazník; Staffan Svärd; Jan O. Andersson; et al. (Scientific Data)
Abstract Diplomonads are anaerobic, flagellated protists, being part of the Metamonada group of Eukaryotes. Diplomonads either live as endobionts (parasites and commensals) of animals or free-living in low-oxygen environments. Genomic information is available for parasitic diplomonads like Giardia intestinalis and Spironucleus salmonicida, while little is known about the genomic arrangements of free-living diplomonads. We have generated the first reference genome of a free-living diplomonad, Hexamita inflata. The final version of the genome assembly is fragmented (1241 contigs) but substantially larger (142 Mbp) than the parasitic diplomonad genomes (9.8–14.7 Mbp). It encodes 79,341 proteins; 29,874 have functional annotations and 49,467 are hypothetical proteins. Interspersed repeats comprise 34% of the genome (9617 Retroelements, 2676 DNA transposons). The large expansion of protein-encoding capacity and the interspersed repeats are the major reasons for the large genome size. This genome from a free-living diplomonad will be the basis for further studies of the Diplomonadida lineage and the evolution of parasitism-free living style transitions.